Socialisation of Medicine (1930)
1930 1930 1930s 2 pages 6. All would be controlled by those concerned, which in a Socialist State are of one class, viz., the workers. 7. A national educational campaign would bring health to the lives and homes of the workers by the best means of propaganda possible. 8. Dr. Bushnell asked the Conference to achieve this through the agency of the workers, who were those concerned, and to organise workers’ health and sickness committees of the I.L.P., which would eventually replace those classes who control at present the lives and health of the working class, but who are not of them. These I.L.P. committees, Dr. Bushnell suggested, could co-opt men and women keen on social and pioneer work, trade unionists, Co-operators, experts, etc., and would function as watch-dogs of the interests of the sick, check inefficiency and inhumanity, control the bureaucratic powers of the permanent officials of the Central and Local Government departments, and promote a vigorous national Socialist health policy in all directions. The proposition was supported officially by the Plymouth, East Ham, and Edinburgh branches, and unofficially by the Clapham, Stourbridge, Launceston, Exeter, Newton Abbot, and Splott (Cardiff) branches, the Devon and Bristol Federations of the S.W. Division of the Independent Labour Party and three Welsh branches. When put to the vote it was carried unanimously. 292/840/1/25